Effect of a Procedural Video on the Practical Fixed Prosthodontic Performance and Stress among Preclinical Dental Students - Inquimbert, Camille; Ferré, Aurélien; Pourreyron, Laurence; Durand, Jean-Cédric (European Journal of Dentistry, 2021)
Objective The purpose of this article was to analyze the effect of an instructional video on practical tutorial and to ascertain whether an instructional video improves students’ performance on practical performance and reduces the stress associated with learning.Materials and Methods A randomized controlled trial was conducted on a group of 78 first-year students. A pretest was conducted by administering questionnaires to evaluate the interest in the use of videos as well as the level of stress. Students were randomly assigned into two groups: control and test. Students assigned to the control group received conventional teaching, while the experimental group received both conventional teaching and watched a video. Thereafter, a satisfaction questionnaire was distributed to each of the groups, and they were awarded a grade.Results A total of 98.7% of students wished to learn fixed prosthodontics through instructional videos, as they believed that the videos could reduce their worry and stress levels. At the end of the first tutorial, the total grade was significantly lower for the test group (p = 0.003). However, the subjective value of stress was significantly lower in the test group (p = 0.0007) as well as the subjective value of tutorial difficulty (p = 0.0004). Students felt that they better understood the objectives of the tutorial “thanks to the video” (p = 0.0001).Conclusion This study did not reveal any improvement in terms of performance when an instructional video was used for tutorials in comparison with the conventional teaching method. However, the results show a reduction in the level of stress.
Keywords: dental students; fixed prosthodontics; instructional video; practical tutorial